Growth Hormone Gene Polymorphism of Donggala Sheep - Dg. Malewa, Amirudin; Hakim, Lukman; Maylinda, Sucik (FAPETKAN UNTAD, 2019)
The study aimed to know the gene polymorphism of growth hormone (GH) of Donggala sheep as potential candidate gene that control the growth characteristics. A total of 50 sheeps from farm community localities (Palu, Central Sulawesi) were analyzed laboratory in BIOMOL FMIPA UB through PCR-RFLP with HinfI enzyme. Results obtained the genotypes of Donggala sheep for PCR-RFLP Hinf1 with genotype AA, AB, BC are 0,933, 0,044 and 0,022. The frequency of A, B and C alleles for Donggala sheep are 0.967, 0.022 and 0.011. PIC value (Polymorphic Information Content) of Donggala sheep is 6.5%. Although PIC value is low, PCR-RFLP Hinf1 finders still have a polymorphic allele variety. Sequence of the three PCR samples also found polymorphisms at the nucleotide base level after comparing them with Lohi breed sheep sequences. Sequence comparisons have a similarity of 97%. Mutations for Donggala sample (20) occurred 16 points while those for Donggala sample (57) occured for 26 points. The point of mutation in the nucleotide base is the cause of polymorphism.Keyword: Donggala sheep, GH genes, PCR-RFLP, Hinf1.